Lipstick effect dan Self-reward di Tengah Tekanan Daya Beli: Analisis Kesenjangan Nilai Syariah dalam Perilaku Konsumsi Muslim Kelas Menengah Urban Pasca-2024 - Ahmad Iqbal Tanjung (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2026)
Indonesian middle-class consumption faces structural pressure. The post-2024 economic downturn has triggered middle-class shrinkage and weakening purchasing power, yet paradoxical patterns persist in lifestyle expenditures among urban Muslim consumers. This study examines the consumption behavior of urban middle-class Muslims amid post-2024 pressure, analyzing how the gap between sharia values and economic reality manifests through the lipstick effect and self-reward, and how religiosity moderates the boundary between permissible consumption (mubah) and concealed wastefulness (israf) within the framework of maqashid al-syariah. A qualitative descriptive-analytical approach with library research design was employed. Data were drawn from primary religious sources (Al-Qur'an and hadith), peer-reviewed journals (2020-2026), and official statistics from BPS and Mandiri Institute (2019-2026). Triangulation of sources ensured analytical rigor. The analysis reveals a paradoxical pattern: while the Indonesian middle class shrunk from 57.33 million (21.45%) in 2019 to 46.7 million (16.6%) in 2025, non-food lifestyle expenditures, particularly transportation, grew 6.4% year-on-year in 2025 (up from 3.2% in 2024). This paradox is explained through the lipstick effect and self-reward as psychological compensation. Three indicators of shift from mubah to israf are identified: frequency accumulation, motive shift toward social validation (FOMO), and disproportionality to personal economic capacity. The findings suggest the need for contextual Islamic financial literacy addressing digital-era consumption (FOMO, paylater), transparent regulation of consumer credit services, and further empirical research using structural equation modeling in metropolitan contexts to test the generalizability of religiosity's moderating role.